2005
DOI: 10.1002/hep.20816
|View full text |Cite
|
Sign up to set email alerts
|

LKM1 autoantibodies in chronic hepatitis C infection: A case of molecular mimicry?

Abstract: Anti-liver-kidney microsome type 1 (LKM1) autoantibodies directed against the cytochrome P450 2D6 (CYP2D6) are considered specific markers of type 2 autoimmune hepatitis, but are also found in 5% of sera from patients chronically infected by hepatitis C virus (HCV). Molecular mimicry between HCV proteins and CYP2D6 has been proposed to explain the emergence of these autoantibodies. Anti-LKM1 autoantibodies from hepatitis C-infected patients were affinity-purified against immobilized CYP2D6 protein and used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 46 publications
0
44
0
Order By: Relevance
“…This study also demonstrated a cross reactivity between the same cytochrome and hepatitis C virus infection which is associated with a high incidence of autoantibody development. More recent work has shown molecular mimicry between cytochrome P2D6 and the NS3 and NS5a proteins of HCV [8] . Cytochrome P2D6 is the target of anti-LKM1 antibodies, the classic diagnostic marker of type 2 autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated a cross reactivity between the same cytochrome and hepatitis C virus infection which is associated with a high incidence of autoantibody development. More recent work has shown molecular mimicry between cytochrome P2D6 and the NS3 and NS5a proteins of HCV [8] . Cytochrome P2D6 is the target of anti-LKM1 antibodies, the classic diagnostic marker of type 2 autoimmune hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Five to 10% of HCV infected patients show autoimmune features that are generally associated with AIH such as anti-LKM1, anti-LC1 and/or anti-SLA autoantibodies [87][88][89] . Purified anti-LKM1 antibodies from HCV-infected patients cross-reacted with the NS3 and NS5a purified proteins sug gesting that CYP2D6 and those viral proteins shared similar structures [90] . A molecular mimicry at the B-cell level between a structural motif of CYP2D6 and HCV proteins could explain the production of anti-LKM1 antibodies in HCV-infected patients [90,91] .…”
Section: Molecular Mimicrymentioning
confidence: 95%
“…Purified anti-LKM1 antibodies from HCV-infected patients cross-reacted with the NS3 and NS5a purified proteins sug gesting that CYP2D6 and those viral proteins shared similar structures [90] . A molecular mimicry at the B-cell level between a structural motif of CYP2D6 and HCV proteins could explain the production of anti-LKM1 antibodies in HCV-infected patients [90,91] . Another link between P450 and HCV was found at the T cell level by Kammer et al [92] who reported T cell cross-reactivity between P450 and the HCV core protein.…”
Section: Molecular Mimicrymentioning
confidence: 95%
See 1 more Smart Citation
“…Centrilobular injury with prominent hepatocyte necrosis and mononuclear inflammation may be seen in some cases of AIH; in most cases, the typical portal-based inflammatory pattern of injury is also present. 17 The current general consensus is that interferon therapy is usually safe in HCV patients with anti-LKM1 autoantibodies. Patients with chronic viral hepatitis should be screened for autoantibodies before starting interferon therapy and monitored carefully.…”
Section: Viral Hepatitismentioning
confidence: 99%